Factors Influencing High Scores in the Food and Nutrition Practical Examinations in Eswatini - Molyn Mpofu; Carol Phindile Dlamini (JETL (Journal of Education, Teaching and Learning), 2020)
The Eswatini Food and Nutrition (FN) examination results have shown that the practical examinations had higher scores than the theory papers, creating negatively skewed distributions. Students were scoring high marks in the FN practical examination component than in theory. This study sought to explore the factors that influence the allocation of high scores in FN practical examinations in Eswatini. A descriptive research design utilizing the qualitative research approach was employed. A sample of 17 participants was purposively selected, comprising of 10 FN teachers, 3 subject Regional Inspectors, 3 Moderators and one Subject Officer. Focus group discussions, interviews and document analysis were used to collect data. Thematic analysis was the tool used to analyse qualitative data obtained from interviews and focus group discussions. The study established that teacher competency levels were low as evidenced by unclear marking schemes. Schools lacked resources, which compromised on the monitoring and supervision of examinations. The study also established that FN practical examination assessment was subjective and that the use of a well-defined marking scheme could minimize the variations. Since FN is a practical subject, students needed to practice cookery tasks during the course of the year, hence students were more likely to excel during the end of year practical examinations. The study recommends discussion of assessment tools and continuous training for examiners before marking of the practical examinations.